Diabetes associated with single gene defects and chromosomal abnormalities - Barbetti, Fabrizio; Ghizzoni, Lucia; Guaraldi, Federica (Frontiers in diabetes / series editors M. Porta, F. M. Matschinsky, 2017)
This volume, written by renowned experts, provides complete coverage of the main genetic conditions associated with diabetes. Divided into five sections, it offers insights into genetic defects involving the pancreatic beta cell, extreme insulin resistance, ciliopathies, obesity and glucose metabolism, chromosomal defects, and other genetic conditions associated with increased susceptibility to diabetes. Other topics include the various subtypes of monogenic diabetes, such as the neonatal form and the Wolfram syndrome, as well as chromosomal defects leading to complex conditions affiliated with diabetes, like Trisomy 21 or Prader-Willi syndrome. There are also chapters dedicated to the poorly explored relationships between metabolism and neurodegenerative disorders like Friedreich's ataxia and muscular dystrophy. This book is a reference for every pediatric and adult endocrinologist and diabetologist, even experienced ones, with an interest in the intricacies and protean aspects of disorders of glucose metabolism secondary to genetic diseases.